Respuesta :

Answer: [tex]x=\frac{1}{3}[/tex]

Step-by-step explanation:

You need to remember the Negative exponent rule:

[tex]a^{-n}=\frac{1}{a^n}[/tex]

Then, having the equation [tex]9x^{-1} - 2 = 25[/tex], you can rewrite it in this form:

[tex]\frac{9}{x} - 2 = 25[/tex]

Now add 2 to both sides of the equation:

[tex]\frac{9}{x} - 2+2 = 25+2\\\\\frac{9}{x}=27[/tex]

Multiply both sides of the equation by "x":

[tex](x)(\frac{9}{x})=27(x)\\\\9=27x[/tex]

 And finally divide both sides of the equation by 27.

The value of "x" is:

[tex]x=\frac{9}{27}\\\\x=\frac{1}{3}[/tex]

Answer:

C on edg

Step-by-step explanation:

ACCESS MORE